Enhancing financial consumer protection in consumer credit industry in Malaysia by establishing a single regulatory body - Ibtisam @ Ilyana Ilias (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
Proponents of consumer protection concur that the need for protection is apparent in the context of the financial consumer. This is due to exploitation, malpractices and oppressive treatment of credit providers comprising of lack of transparency, high interest rate, hidden charges, unreasonable penalty charges, misleading advertisement, aggressive marketing, unsolicited products and credit advance as well as unfair debt collection practices. The problem is aggravated by fragmented institutional approach regulating a wide-array of consumer credit industry. This primarily leads to inconsistent supervision and enforcement of the law and different levels of protection accessible to a different range of financial consumers depending on the regulator responsible for safeguarding their interests. Confusion is anticipated to arise among consumers as to proper body that should be relied on when their rights are infringed. Hence, comprehensive protection is not achieved by the present framework. These disturbing problems stimulate this study which fundamentally aims at examining the bodies regulating consumer credit industry in Malaysia and the lacunae in the present framework. It also aims to explore the Islamic perspective of financial consumer protection in Islamic consumer credit industry. Other cardinal objectives include to scrutinise the approaches adopted by selected jurisdictions in establishing institutional framework of this industry and eventually to propose recommendations to improve the existing institutional framework in consumer credit regulation. In achieving the said objectives, doctrinal, qualitative and comparative law research methodologies are employed. One major finding of this study is the absence of a single institution to regulate the industry which leads to inconsistent and inadequate protection to all financial consumers dealing with consumer credit. The study recommends the setting up of one regulatory body responsible for all financial consumers. It is hoped that this study will benefit the regulators in reforming the existing framework and ultimately enhancing the protection of the financial consumers as the main stakeholder of this study.